Spatiotemporal Analysis of Land Use and Land Cover Change in Banjarbaru City (2002–2022) Using Google Earth Engine - Muhammad Nurul Huda; Shalsabilla Aulia Putri; Denisa Aulia Pratiwi; Salsabila Rahma; Azril Chairil; Nur Kahfi Mukhlisin Anwar; Listyo Yudha Irawan (Universitas Lambung Mangkurat, 2026)
This study analyzes spatiotemporal changes in land use and land cover (LULC) in Banjarbaru City over a twenty-year period (2002–2022) to examine the reorganization of its urban spatial structure in relation to economic growth, housing demand, and environmental conditions. Multi-temporal land cover data from the GLC-FCS30D dataset were processed on the Google Earth Engine platform, reclassified into seven dominant land-cover categories, and validated using 180 stratified validation points cross-checked against high-resolution satellite imagery. The mapped patterns indicate that built-up areas expanded from a compact urban core into a continuous urban fabric, while plantation and shrubland/forest cover declined substantially and agricultural land increased in spatial extent toward the urban periphery. Open and bare land also expanded as transitional land states associated with ongoing development. These trajectories correspond to broader structural changes documented in regional economic and housing studies, including increased residential land absorption driven by public housing affordability programs and shifts in sectoral economic contribution. The spatial restructuring of green and wetland areas indicates increasing fragmentation and reduced ecological buffering, aligning with research demonstrating declining carbon storage and heightened hydrological sensitivity as vegetated land is converted to urban surfaces. The results present a comprehensive characterization of Banjarbaru’s land transition dynamics and provide a spatial basis for evaluating urban planning, green space management, and sustainability strategies.